Resveratrol derivatives as a pharmacological tool. Issue 1 (4th July 2017) - Biasutto, Lucia; Mattarei, Andrea; Azzolini, Michele; La Spina, Martina; Sassi, Nicola; Romio, Matteo; Paradisi, Cristina; Zoratti, Mario
Abstract: Prodrugs of resveratrol are under development. Among the long‐term goals, still largely elusive, are (1) modulating physical properties (e.g., water‐soluble derivatives bearing polyethylene glycol chains), (2) changing distribution in the body (e.g., galactosyl derivatives restricted to the intestinal lumen), (3) increasing absorption from the gastrointestinal tract (e.g., derivatives imitating the natural substrates of endogenous transporters), and (4) hindering phase II metabolism (e.g., temporarily blocking the hydroxyls), all contributing to (5) increasing bioavailability. The chemical bonds that have been tested for functionalization include carboxyester, acetal, and carbamate groups. A second approach, which can be combined with the first, seeks to reinforce or modify the biochemical activities of resveratrol by concentrating the compound at specific subcellular sites. An example is provided by mitochondria‐targeted derivatives. These proved to be pro‐oxidant and cytotoxic in vitro, selectively killing fast‐growing and tumor cells when supplied in the low micromolar range. This suggests the possibility of anticancer applications.